Om God in goed en kwaad te sien. Oor twee vorme van teodisee - Brand, Gerrit (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Seeing God in good and evil: Two forms of theodicy The author distinguishes between two theodicy questions: (1) Why does God permit evil and suffering to happen? (2) Are evil and suffering compatible with the existence of God? In answer to the first question: the author pleads ignorance. We cannot know God’s thoughts and motives. He does show, however, that there are several possible motives and reasons. The answer to the second question is shown to be positive. The author uses the tsunami of 2004 as his main example, and shows in his discussion that human responsibility plays a more important role than is often thought. Following Vincent Brümmer, he argues that in the final resort, our view of the balance of good and evil in the world is a question of religiously motivated interpretation.